"Brasil, mostra tua cara" : um estudo sobre a relação entre a marca-país Brasil e as dimensões de confiança, consideradas a partir da cartografia de ações comunicacionais do Ministério do Turismo - Picinini, Rudinei (My University, 2023)
The present research has as focus the relations between the Brazil country brand and the different dimensions of trust, considered from a cartography of communication actions of the Brazilian Ministry of Tourism through digital technologies, during the Covid-19 pandemic. The general objective of this research is to discuss the relation between the Brazil country brand and dimensions of trust, considering from the cartographic communication actions of the Brazilian Ministry of Tourism through digital technologies, during the Covid-19 pandemic. Therefore, the specific objectives of this study are: a) present the country brand concept and establish relations with the Brazil country brand; b) present and discuss the concept of trust; c) map the communicational actions of the Ministry of Tourism in the digital technologies, during the Covid-19 pandemic; d) discuss relations of communication actions of the Ministry of Tourism with the country brand and dimensions of trust. Thereby, for the construction of this research, the following theoretical references were consulted: to contextualize the trust concept, authors as Luhmann (2000, 2017) and Terres and Santos (2010, 2011, 2013, 2015) were used; to discuss digital technologies Lévy (2010) and Monteiro (2017); to discuss tourism Baptista (2020) and Moesch and Beni (2016); recent articles to contextualize the Covid-19 pandemic were used as well. The methodological strategy chosen was the Cartography of Knowledge (BAPTISTA, 2014, 2022) associated with Rhizomatic Matrices (BAPTISTA, 2017, 2020, 2022). The Cartography of Knowledge is composed of five different investigative trails, with a plural methodological and processual orientation: `Intertwining Knots? of research, Personal Knowledge, Theoretical Knowledge, Production Plant and Intuitive Dimension of Research. In this study, it was possible to verify that communication actions of the Ministry of Tourism of Brazil, developed during the pandemic Covid-19, didn't collaborate to strengthen attributes connected with different cognitive and affective dimensions of trust on the Brazil country brand. These actions were verified regarding the narratives that circulated in the digital media ecosystem and the information recommended by WHO (2020) and UNWTO (2020a, 2020b). [resumo fornecido pelo autor]
A presente pesquisa tem como foco as relações entre a marca-país Brasil e as dimensões de confiança, consideradas a partir da cartografia de ações comunicacionais do Ministério do Turismo brasileiro via tecnologias digitais, durante a pandemia Covid-19. Nesse sentido, o objetivo geral desta pesquisa é discutir a relação entre a marca-país Brasil e as dimensões de confiança, consideradas a partir da cartografia de ações comunicacionais do Ministério do Turismo brasileiro via tecnologias digitais, durante a pandemia de Covid-19. Assim, os objetivos específicos deste estudo são: a) apresentar o conceito de marca-país e estabelecer relações com a marca-país Brasil; b) apresentar e discutir o conceito de confiança; c) cartografar ações comunicacionais do Ministério do Turismo via tecnologias digitais, durante a pandemia de Covid-19; d) discutir relações das ações comunicacionais do MTUR com a marca-país e as dimensões de confiança. Dessa forma, para a construção desta pesquisa, foi utilizado o seguinte referencial teórico: para contextualizarmos o conceito de confiança, os autores como Luhmann (2000, 2017) e Terres e Santos (2010, 2011, 2013, 2015); para a tecnologia, Lévy (2010) e Monteiro (2017); para o turismo, Baptista (2020) e Moesch e Beni (2016); assim como artigos recentes para contextualizar a Covid-19. Como estratégia metodológica, foi escolhida a Cartografia de Saberes (BAPTISTA, 2014, 2022), em associação às Matrizes Rizomáticas (BAPTISTA, 2017, 2020, 2022). A Cartografia de Saberes é composta por cinco trilhas investigativas, com orientação plurimetodológica e processual: `Entrelaços Nós? da Pesquisa, Saberes Pessoais ou Dimensão Subjetiva, Saberes Teóricos-Conceituais-Bibliográficos, Usina de Produção ou Trama dos Fazeres e Dimensão Intuitiva da pesquisa. Neste estudo, foi possível verificar que as ações comunicacionais do Ministério do Turismo no Brasil, desenvolvidas durante a pandemia de Covid-19, não colaboram para o fortalecimento dos atributos ligados às dimensões cognitiva e afetiva da confiança na marca-país. Essas ações foram verificadas em relação às narrativas que circularam no ecossistema midiático digital e as informações recomendadas pela OMS (2020) e OMT (2020a, 2020b). [resumo fornecido pelo autor]
Keywords: Turismo - Brasil; Características nacionais - Brasil; Brasil. Ministério do Turismo; Tourism - Brazil; National characteristics - Brazil; Brazil. Ministry of Tourism